Hybrid aesthetics classification in Malay neo-classicality reinventing identity through aristocratic structures - Jahn Kassim, Puteri Shireen; Abdul Majid, Noor Hanita; Md. Sharif, Harlina; Raja Abdul Kadir, Tengku Anis Qarihah (Readers Insight, 2018)
South East Asian architecture identity in urban centres has been generally focused on either timber vernacular identity or large masonry building. The local agenda is increasingly crucial amidst the importance of tourism and city-branding which necessitate the enculturation of urbanism within an overall resistance to extensive globalisation. Traditional public typologies such as palaces and mosques in Asia hold the promise of resources that can add place-branding and identity to towns and cities, while at the same time a high resource for new forms and patterns. Through an extensive morphological and evolutionary mapping of such typologies, the aim is to develop a classification that can define stylistic categories and aesthetic predispositions, such that these classifications can be used to manage, market and enhance such historical narrative of towns and contribute to identity-making in the urban-scape. Throughout the Asian region, particularly in nations previously under Colonisation, there is a common resource of public typologies which have not been identified in terms of early stylistic changes and nuances that would contribute towards heightening of Asia’s common heritage and increasing awareness of such hybrid forms. These, if classified and defined, can consolidate towards the continuing agendas of identity-making in cities; including the management of preservation and conservation actions and policies. Many of these structures have been neglected as they are either seen as vernacular or part of a Colonial narrative and imprint. Many of these individual heritage preservation efforts has been the initiative of their local sites and communities. The present privileging of national agendas and interest over regional collective action is not in the interest of awareness and action. In the past, national barriers have actually amplified the problem and reduced the potential of asserting the global and regional significance of such structures.